Acetic Acid, the Active Component of Vinegar, Is an Effective Tuberculocidal Disinfectant - Claudia Cortesia (American Society for Microbiology, 2014)
ABSTRACT Effective and economical mycobactericidal disinfectants are needed to kill both Mycobacterium tuberculosis and non-M. tuberculosis mycobacteria. We found that acetic acid (vinegar) efficiently kills M. tuberculosis after 30 min of exposure to a 6% acetic acid solution. The activity is not due to pH alone, and propionic acid also appears to be bactericidal. M. bolletii and M. massiliense nontuberculous mycobacteria were more resistant, although a 30-min exposure to 10% acetic acid resulted in at least a 6-log10 reduction of viable bacteria. Acetic acid (vinegar) is an effective mycobactericidal disinfectant that should also be active against most other bacteria. These findings are consistent with and extend the results of studies performed in the early and mid-20th century on the disinfectant capacity of organic acids. IMPORTANCE Mycobacteria are best known for causing tuberculosis and leprosy, but infections with nontuberculous mycobacteria are an increasing problem after surgical or cosmetic procedures or in the lungs of cystic fibrosis and immunosuppressed patients. Killing mycobacteria is important because Mycobacterium tuberculosis strains can be multidrug resistant and therefore potentially fatal biohazards, and environmental mycobacteria must be thoroughly eliminated from surgical implements and respiratory equipment. Currently used mycobactericidal disinfectants can be toxic, unstable, and expensive. We fortuitously found that acetic acid kills mycobacteria and then showed that it is an effective mycobactericidal agent, even against the very resistant, clinically important Mycobacterium abscessus complex. Vinegar has been used for thousands of years as a common disinfectant, and if it can kill mycobacteria, the most disinfectant-resistant bacteria, it may prove to be a broadly effective, economical biocide with potential usefulness in health care settings and laboratories, especially in resource-poor countries.